The Role of Phonetics in Teaching ESL Learners - Komali Prakash (Journal of English Language Teaching, 2015)
Phonetics is usually regarded as a subject by itself and teachers of English consider it a tool in accent neutralization at the most. In this context, this paper shows the essential role of phonetics in the teaching of English as a Second Language (ESL) with focus on segmental (phonemes) and suprasegmental (stress, accent, rhythm and intonation) features. For teachers, who have had a good model of English pronunciation in their growing years, the awareness may be intuitive and the features may have become part of their language. But for the others, who teach ESL, learning the nuances of phonetics may be considered a part of their continuing professional development (CPD).